Study On The Accuracy Of Squeeze Film Damping Calculation With Finite Element Analysis - Harun, Muhammad Syakir (2013)
Squeeze film damping due to the air trapped between oscillating membrane structure and a fixed substrate is a critical consideration in the design of MEMS devices because it can adversely affect the dynamic behaviour of the system. Therefore, the development of MEMS depends highly on the modelling and numerical simulation in order to optimize and verify their design before the batch production process. In this thesis, a method to model squeeze film damping with finite element approach to attain sufficiently high accuracy while considerably reducing the degrees of freedom is proposed, and its effectiveness is studied by comparing with other methods. The numerical analysis was performed using commercial ANSYS software. The structures were modelled using three-dimensional (3D) element and two-dimensional (2D) element. Results obtained by finite element models are compared with existing experimental measurements and analytical solutions. It was found that for the computation of damping coefficient, two-dimensional model yields slightly similar accuracy with three-dimensional model with respect to experimental data for low number of holes. In contrast, for highly perforated membranes, the proposed two-dimensional model is shown to be more accurate. The results clearly validate the proposed model to achieve good accuracy for damping coefficient solution while consuming considerably less computer time and memory.